Exploring Service Quality, Customer Satisfaction and Customer Loyalty in the Taiwan Mobile Telecommunication - Danang Kisworo (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2013)
The launch of nationwide Mobile Number Portability (MNP) in October 2005 has taken the Taiwanmobile telecommunication industry one step forward . The implementation of MNP has given anotherchallenge for the mobile service providers to maintain their loyalty of existing customer as customers areallowed to retain their existing telephone number when switching from one mobile service provider toanother. Under such circumstances, the pursuit of customer loyalty appears to be an essential goal of thecompanies' sustainable competitive advantage and growth. In response to the challenges, mobile serviceproviders are aggressively launching various innovative and attractive marketing campaigns and promotionswith the aim to retain customer loyalty. The objectives to carry out this research are to investigate therelationship between service quality and customer satisfaction and to investigate the relationshipbetween customer satisfaction and customer loyalty in the Taiwan mobile telecommunication market.This study adopts five dimensions of SERVQUAL instrument to measure service quality in the mobiletelecommunication industry, such as tangibles, reliability, responsiveness, assurance and empathy. A seriesof Questionnaire provide and distribute to explore the mobile service providers’ customer. The five-pointLikert scale that ranged from 1=strongly disagree to 5= strongly agree. Hypotheses testing are needed toobtain the objective of this research by using Regression analysis. Result shows that the dimensions ofservice quality such as tangibles, responsiveness, assurance and empathy have significant effect tocustomer satisfaction. Furthermore, customer satisfaction was found to have significant positive effecton customer loyalty in the Taiwan mobile telecommunication industry.